Case pile wave equation analysis: CAPWAPC. Evaluation of driven piles. - Edde, Robert D. (University of Ottawa (Canada), 1991)
One of the most important aspects of a piled foundation is the bearing capacity of the individual piles. Correct quantitative evaluation of the pile capacity during pile driving requires the use of dynamic monitoring by means of the Pile Driving Analyzer. These monitoring data are combined with a wave equation analysis and processed using a special software called CAPWAP. The CAPWAP analysis is an iterative procedure whereby the calculated force trace is adjusted to agree with the one measured. The main objective of the thesis study is to produce a statistical indication of the natural variation between the results from a CAPWAP analysis performed on blows within the same soil layer. More specifically, for three selected case histories, the natural variation is studied between contiguous blows of the pile capacity, the resistance distribution between the shaft and the toe, and of the soil dynamic parameters (quakes and damping) as determined in the CAPWAP analysis. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.